Analysis of Potentially Modifiable and Unmodifiable Risk Factors of Myocardial Infraction: Systematic Review - Abudaqa, Loai; Hegazi, Shady; Al-Swari, Nabil; Gharbi , Maro; Alyasseen, Osama; Lozon, Hadeel; Alaila, Farah; Al Nooryani, Arif (PT Inovasi Pratama Internasional, 2023)
Myocardial infarction is a leading cause of death, disability, and decreased productivity worldwide, particularly in relation to cardiovascular disease. The aim of this study was to assess the contribution of both modifiable and non-modifiable risk factors to the incidence of myocardial infarction in a large population (32,585 patients; 26,020 male and 6,564 female). An extensive search was conducted on databases such as PubMed, Google Scholar, Scopus, Medline, and Web of Science, limited to full-text articles written in English and published from 2015 onwards, using keywords such as